PENINGKATAN MUTU PENDIDIKAN DI MADRASAH TSANAWIYAH NEGERI 4 BUTON BERBASIS KOMPETENSI ENTREPRENEURSHIP KEPALA MADRASAH: (Quality Improvement of Education in Madrasah Tsanawiah Negeri 4 Buton Based on Competence of Entrepreneurship Head of Madrasah) - Dafik, La (Uniqbu Journal of Social Sciences, 2023)
The aim of this paper is to find out how to improve the quality of education at Madrasah Tsanawiyah Negeri 4 Buton based on the Entrepreneurship Competency of the Madrasa Head. The method used in this research is qualitative research. Where the researcher conveys the data in accordance with the information obtained so that it is described in the form of sentences. While the type of research used by researchers in this study is a type of descriptive research. Where this type of descriptive research only describes and describes phenomena, symptoms, events, and incidents that occur. The research results show that; The Madrasah Head seeks to improve the quality of Education in Madrasahs by increasing existing teacher resources in Madrasas such as improving teacher performance by providing guidance, workshops, and socialization even the Madrasah Head provides opportunities for teachers to take part in education and training held by other agencies, seeking to improve the performance of each madrasah manager by evaluating performance and achieving targets by making an agenda for internal Madrasah meetings so that inadequate infrastructure can be used as optimally as possible, as well as seeking to increase student achievement in Madrasahs with extracurricular training so that they can compete with other Madrasas in international competition Madrasas and other public schools. The entrepreneurial competence of madrasah heads includes competencies that exist in an entrepreneur including being able to think creatively and innovatively, namely in the form of processing plastic waste utilization activities, creating fish farming business opportunities, and creating rote learning strategies. Work hard to achieve success with high perseverance, not afraid of failure, and always try to find solutions. Have the motivation to successfully carry out their main duties and functions as the head of the madrasa by providing encouragement to all madrasa residents. Never give up by never giving up on carrying out every activity. And have entrepreneurial instincts in managing madrasah activities by involving students and giving awards to outstanding students